Design and Development of Smart Irrigation System Using Internet of Things (IoT) - A Case Study - G. Sasi Kumar, G. Nagaraju, D. Rohith and A. Vasudevarao (Nature Environment and Pollution Technology, 2023)
With India’s population growing at a rapid pace, traditional agriculture will have a tough time meeting future food demands. Water availability and conservation are major concerns for farmers. This paper aims to discuss the aspects related to designing and fabricating an automatic irrigation system using the Internet of Things (IoT) which will save the farmer’s time and money significantly. Human intervention in fields will be reduced. Changes in soil moisture are detected by soil moisture sensors and irrigation is automated using IoT. The proposed system is most economical for underdeveloped places because it is very cost-effective. Based on the soil moisture content, the sensor detects and sends signals to the node MCU, which activates the motor. When the plants receive enough water, the motor automatically shuts off. The user will be alerted about the soil’s moisture content through his mobile phone. The proposed smart irrigation system is implemented at our campus which conserves energy and water.